Retain and reuse of knowledge using CAD-models - Lundin, Michael (2009)
Knowledge and information is two very general terms used in all kinds of contexts and certainly key aspects of any product development. An area with issues in regard to both these is that of storage and retrieval, one which really has been taken to heart during this master thesis. Aimed towards retention and reuse of knowledge in computer-based 3D-models this thesis has been conducted for the division for Computed Aided Design at Luleå University of technology and further applied to Gestamp Hardtech. Gestamp Hardtechs main efforts lie in development and manufacturing of structural automotive components, side impact beams, bumpers and various posts are among these. Most significant for Gestamp hardtech and their components is their press-hardening technology. A previous master thesis has been conducted at GHT, more specifically on their research and development department for side impact beams. That thesis resulted in a set of tools for start-up model generation, interactive beam customisation and optimisation using a basic graphical user interface. Research related to knowledge incorporation with the actual CAD models has also been and still are continuously researched at the division for Computer Aided Design. The overall aim of this thesis has been to increase knowledge sharing throughout the product development process. The first thesis part applied this thinking to Gestamp Hardtechs initial quotation design and more specifically to how production cost could be calculated and presented to the designer during initial SIB development. As for the second part, focus lay on development of a method for retention and reuse of information throughout the product development process, all incorporated within the CAD model. Two different tools were created using NX and the Knowledge Based Engineering support it provides through Knowledge Fusion and NX Open. These two applications based on the same basic principles surrounding knowledge management has together ensured that knowledge is shared in a two-way channel during ...